Humans, nature, and birds : science art from cave walls to computer screens - Wheye, Darryl (Yale University Press, 2008)
"This book invites readers to enter a two-floor virtual "gallery" where 60-plus images of birds reflecting the accomplishments of human pictorial history are on display. These are works in a genre the authors term Science Art - that is, art that says something about the natural world and how it works. Darryl Wheye and Donald Kennedy show how these works of art can advance our understanding of the ways nature has been perceived over time, its current vulnerability, and our responsibility to preserve its wealth."--Jacket